PENGARUH KEMANDIRIAN DAN EFEKTIFITAS KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DENGAN BELANJA MODAL SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada PemerintahKabupaten/Kota di Provinsi Jawa Tengah Periode 2013-2016) - Anggi Pratiwi, 14.05.52.0131; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze empirically about the influence of independence and effectiveness of regional finance to economic growth with capital expenditure as moderator variable at Regency and City in Central Java Province 2013-2016. The economic growth was measured by using a ratio of GDP growth. Population in this research is all Regency and City in Central Java Province. This research data in the form of secondary data in the form of LRA and Central Java Province PDRB table year 2013-2016.The analysis technique usedis residual test.The data that have been collected is analyzed first by multiple linear regression and then done hypothesis testing with SPSS 19.0. Based on the results of research can be concluded that the regional financial independence and effectiveness does not affect the economic growth. In addition, capital expenditure can not be used as a moderating variable in this studybecause capital expenditure can not strengthen the links between the independence and effectiveness of regional finance to economic growth at Regency and City in Central Java Province Keywords: Independence of regional finance, Effectiveness of regional finance, Economic Growth, Capital Expenditure